A Pharmaceutical Composition Comprising A Liposomal Formulation Of Efavirenz, Its Preparation And Application Thereof - Balasaheb Nale, Dhanashree; Sudhir, Shinde Nalini; Abbaso, Malgunde Anuja; Sambhajirao, Kadam Shrikant; Shivajirao, Bandal Rajendra; Moulalli, Sayyad Naziya (Journal of Neonatal Surgery, 2025)
In many countries, Efavirenz is the primary non nucleotide reverse transcriptase inhibitor for first-line antiretroviral therapy. It is an orally active antiviral drug that is specific for human immunodeficiency virus type 1 (HIV-1). Its effectiveness is due to its lengthy half-life, which ranges from 52 to 76 hours after numerous doses. The medication is poorly soluble in water. One of the most difficult difficulties for formulation scientists in the research sector will be the oral delivery of poorly soluble drugs. We intended to investigate effective encapsulation of efavirenz (EFV, which is one of the powerful (ARVs) using varied mass ratios of crude soybean lecithin and cholesterol, since the liposome is the most clinically successful DDS and yet is often investigated for ARVs delivery